Strategi Sekolah dalam Mencegah dan Menangani Kekerasan Seksual Berbasis Perspektif Feminis Kritis: Studi Etnografi Kebijakan - Okta Rosfiani; Ahmad Najihan Maulana; Muhamad Farhan; Zakki An Nafis; Ammara Lutfatunnisa; Cecep Maman Hermawan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Sexual violence in educational environments, including Islamic boarding schools (pesantren), is a serious issue that requires appropriate and timely prevention and response strategies. However, research on policy implementation in pesantren that apply complete gender segregation remains limited, particularly studies employing a critical feminist approach to uncover the power relations underlying such policies. This study aims to examine the prevention and response mechanisms for sexual violence at Madrasah Aliyah Ummul Qura Pondok Cabe and to analyze how the institution addresses patronal power relations within its existing policy framework. This ethnographic study was conducted through direct observation, in-depth interviews with madrasah principals, teachers, dormitory administrators, and students, as well as an analysis of institutional policy documents. The main findings reveal that complete gender segregation effectively reduces heterosexual violence but simultaneously creates new vulnerabilities in the form of same-sex violence within homogeneous dormitory environments. In response to this issue, the institution established Student Regulations and a Student Code of Ethics that are gender-neutral. The theoretical significance of this study lies in the deconstruction of the doctrine of students’ absolute obedience to teachers or kiai through the internalization of the principle la tha'ata li mahlukin fi ma'shiyatil khaliq, which empowers students to reject and report abuse committed by authority figures. In terms of response mechanisms, the institution implements a zero-tolerance policy through sanctions such as expulsion and direct reporting to the police in cases involving serious criminal offenses, prioritizing victims’ justice over institutional reputation. The limitation of this study lies in its single-site scope; therefore, broader generalizations should be made with caution.